Islamophobia dalam Perspektif Sosiologi Islam (Analisis terhadap Akar Perilaku Diskriminatif) - Mohammad Hikam Rofiqi; Isa Anshori (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
This article discusses islamophobia from a social perspective by analyzing the roots of discriminatory behavior that occurs against muslims. This research involves a large population and shows that a person's level of trust in muslims is greatly influenced by social interactions and how they identify the behavior patterns of a muslim. This research was conducted with the aim of ensuring that people are able to understand islam through the lens of harmonious and religious beliefs, not as an unwarranted fear. A systematic approach in discussing this topic includes literature studies as well as netnography published through digital media. This finding emphasizes the importance of people's interpretation of the implications of the islamic religion in accordance with what is taught. This research involves the steps of analyzing literature from previous scientific work, by applying a qualitative descriptive approach. The data interpretation method used is netnography-based, which aims to explore and analyze content in depth. This approach was chosen as a framework to outline the current research, allowing a better understanding of the phenomenon under investigation.